Mechanisms of post-contraction activation in skeletal muscle - Uematsu, A.; Sekiguchi, H.; Kobayashi, H.; Tsuchiya, K.; Hortobágyi, T.; Suzuki, S. (The Journal of Physical Fitness and Sports Medicine, 2012)
This review provides evidence for the task-, intensity-, and duration-specific modulation of twitch, spinal, corticospinal and cortical responses recorded up to ~18 min after the end of a muscle contraction produced by artificial and voluntary muscle activation in animal and human experimental models. Animal data revealed facilitation in spinal excitability after tetanic contraction; a phenomenon confirmed by human experiments using artificial, as well as voluntary, activation of muscle. There is evidence for a strong task-specific potentiation of spinal excitability associated with shortening and high intensity isometric contractions in contrast to depression after lengthening contractions. Contraction duration-specific effects suggest that when a contraction is performed to fatigue, post-exercise spinal excitability tends to decrease. Data from a limited number of transcranial magnetic brain stimulation studies suggest that, akin to spinal excitability, voluntary muscle contraction produces corticospinal and cortical excitability-associated changes. Of possible functional relevance, concerning these data, is that potentiation and depression in neural excitability can shape the mechanisms of how acute responses to exercise accumulate and convert to chronic adaptations. Of clinical relevance is that an even better understanding of the post-contraction effects would provide the opportunity for therapists to set exercise parameters according to the goals of therapy and need of patients and athletes to up/ down-regulate spinal, corticospinal, and cortical activity.